Androstenediol Reduces Demyelination-Induced Axonopathy in the Rat Corpus Callosum: Impact on Microglial Polarization - Kalakh, Samah; Mouihate, Abdeslam (Frontiers in Cellular Neuroscience, 2017)
Aims: We have previously shown that the neurosteroid androstenediol promotes remyelination following gliotoxin-induced demyelination. However, the impact of this androstenediol on axonal recovery is not yet known. In the present study, we investigated the impact of androstenediol on axonal integrity following a focal demyelination in the corpus callosum. Methods: A 2μl solution of either ethidium bromide (0.04%) or pyrogen-free saline were stereotaxically injected into the corpus callosum of Sprague Dawley rats. Each of these two rat groups was divided into two subgroups and received daily subcutaneous injections of either androstenediol (5mg/kg) or vehicle. The brains were collected at 2, 7 and 14 days post-stereotaxic injection. Immunofluorescent staining was used to explore the impact of androstenediol on axonal integrity (neurofilament-M) and microglial activation (ionized calcium binding adapter molecule 1). The inducible nitric oxide synthase and arginase-1, two major markers of microglial polarization towards the proinflammatory M1 and the regulatory M2 phenotypes respectively, were monitored using western blot. Results: Androstenediol increased the density of neurofilament fibers and decreased the extent of axonal damage in the vicinity of the demyelination lesion. Androstenediol-induced decrease in axonal damage was manifested by decreased number of axonal spheroids at both 2 and 7 days post-demyelination insult. This reduced axonopathy was associated with decreased expression of iNOS and enhanced expression of Arginase-1 during the acute phase. Conclusion: These data strongly suggest that androstenediol reduces demyelination-induced axonal damage, likely by dampening the local inflammatory response in the white matter and shifting microglial polarization towards a reparative mode.